2019
DOI: 10.1016/j.jaci.2018.10.065
|View full text |Cite
|
Sign up to set email alerts
|

Serious asthma events with mometasone furoate plus formoterol compared with mometasone furoate

Abstract: Background: The safety of long-acting b-agonists added to inhaled corticosteroids for the treatment of persistent asthma has been controversial. Objective: We sought to determine whether administering formoterol in combination with mometasone furoate increases the risk of serious asthma outcomes (SAOs) compared with mometasone furoate alone. This clinical trial is registered as NCT01471340. Methods: We conducted a 26-week, randomized, double-blind trial in adolescent and adult patients (> _12 years) with persi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Large clinical safety studies of budesonide-formoterol and other approved ICS-LABA combinations given as maintenance therapy, initiated by the US FDA [26], have dispelled any lingering safety concerns (or misperceptions) relating to serious asthma-related AEs with LABA treatment when taken with an ICS from the same device [27][28][29][30]. The FDA subsequently removed the boxed warning from all approved ICS-LABA combinations [31].…”
Section: Discussionmentioning
confidence: 99%
“…Large clinical safety studies of budesonide-formoterol and other approved ICS-LABA combinations given as maintenance therapy, initiated by the US FDA [26], have dispelled any lingering safety concerns (or misperceptions) relating to serious asthma-related AEs with LABA treatment when taken with an ICS from the same device [27][28][29][30]. The FDA subsequently removed the boxed warning from all approved ICS-LABA combinations [31].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, findings from the phase 2 study provide important supporting information on cardiovascular safety of the MF/IND fixed-dose combination in asthma. In 2010, the US Food and Drug Administration (FDA) mandated that companies marketing LABAs for asthma perform 26-week randomized trials of their ICS/LABA products versus the respective ICS controls, with the primary endpoint of asthma-related intubation or death [22][23][24][25]. Because the cause of death was described for all fatal cases, the incidence of cardiovascular death can be quantified based on the published data (Supplementary Table 9).…”
Section: Laba Effectsmentioning
confidence: 99%
“…In summary, these trials found that the ICS-LABA combinations were effective in reducing asthma exacerbations requiring corticosteroids and did not signifi cantly increase the risk of serious adverse asthma outcomes. [4][5][6][7] Despite the removal of the boxed warning, no ICS-LABA combination has an FDAapproved indication for treating acute bronchospasm on an as-needed basis, as the GINA 2019 guidelines recommended. 8…”
Section: ■ What Is the Expected Clinical Impact?mentioning
confidence: 99%